World Health Organization dimensions of adherence to antiretroviral therapy: A study at antiretroviral therapy centre, Aligarh - Yasir Alvi; Najam Khalique; Anees Ahmad; Haroon Subhan Khan; Nafis Faizi (Wolters Kluwer Medknow Publications, 2019)
Introduction: With the availability of antiretroviral therapy (ART) and subsequent change in the HIV/AIDS disease dynamic to a chronic manageable disease, adherence studies have received increasing attention. However, there is a paucity of studies that have considered World Health Organization (WHO) dimensions of adherence to ART. Therefore, this study was conducted with the objectives of determining the prevalence of adherence and the association of various factors across five WHO dimensions to adherence. Methods: A cross-sectional study was carried out at the ART Centre, Aligarh. A total of 440 adult patients, taking treatment from the ART Centre, Aligarh were selected. A self-reported instrument of missing pills was used to measure adherence. Various factors across five WHO dimensions were studied. Results: Prevalence of adherence in our study was 81.3%. Among the five dimensions of adherence, distance from home (odds ratio [OR] 0.980; 95% confidence interval [CI] 0.964-0.997) among socioeconomic determinants, frequent adherence counseling (OR 8.737; 95% CI 4.076-18.727) among health system-related, drug regimen (OR 2.202; 95% CI 1.023-4.738) and absence of side effects (OR 3.293; 95% CI 1.473-7.365) among therapy related, absence of substance abuse (OR 2.747; 95% CI 1.209-6.243), and perceived change in health status (OR 4.196; 95% CI 1.613-10.915) among patient-related dimension were found to be significantly associated with adherence to ART, while clinical condition dimension did not play a significant role. Conclusion: The ART adherence rate is still below satisfactory levels for long-term viral load suppression. WHO multidimensional approach - which was found to be quite relevant in our study setting - could be applied to effectively solve the adherence problem in our country.